1997
DOI: 10.1016/s0092-8674(00)80464-x
|View full text |Cite
|
Sign up to set email alerts
|

Ectopically Expressed CAG Repeats Cause Intranuclear Inclusions and a Progressive Late Onset Neurological Phenotype in the Mouse

Abstract: The mutations responsible for several human neurodegenerative disorders are expansions of translated CAG repeats beyond a normal size range. To address the role of repeat context, we have introduced a 146-unit CAG repeat into the mouse hypoxanthine phosphoribosyltransferase gene (Hprt). Mutant mice express a form of the HPRT protein that contains a long polyglutamine repeat. These mice develop a phenotype similar to the human translated CAG repeat disorders. Repeat containing mice show a late onset neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
221
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 346 publications
(235 citation statements)
references
References 31 publications
13
221
1
Order By: Relevance
“…Overwhelming evidence indicates that the misfolding of proteins that contain polyQ expansions, but are otherwise unrelated, is a central element in the pathology of each disease. The polyQ expansion is the common determinative factor in their misfolding (39). By extension, then, our studies in yeast hold promise for investigating the mechanisms underlying all of these pathologies.…”
Section: Discussionmentioning
confidence: 85%
“…Overwhelming evidence indicates that the misfolding of proteins that contain polyQ expansions, but are otherwise unrelated, is a central element in the pathology of each disease. The polyQ expansion is the common determinative factor in their misfolding (39). By extension, then, our studies in yeast hold promise for investigating the mechanisms underlying all of these pathologies.…”
Section: Discussionmentioning
confidence: 85%
“…The pathogenic effect of these expanded glutamine repeats is independent of the polypeptide in which it is present since the ''in vitro'' insertion of CAG repeats in nondisease protein can also induce neurodegeneration ''in vivo'' (Ordway et al 1997). Also, the susceptibility of Drosophila to glutamine repeat disease has been demonstrated, very elegantly, by two studies: in one of them (Warrick et al 1998) the expression, in the compound eye, of the carboxy-terminal fragment of ataxin-3 containing 27 glutamines (the wildtype number) plus the 43 downstream amino acids does not seem to cause any deleterious effect, while the expression of the same construct but with a 78 amino acid long expanded glutamine repeat present in patients with Machado-Joseph Disease shows late-onset progressive cell degeneration, with neurons being particularly sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…The factors that influence the vulnerability of different subpopulations of neurons in the various human polyglutamine-associated diseases are still not known. It has been demonstrated that if a long polyglutamine tract is engineered into a protein that normally lacks such a domain, the resulting mice display symptoms and neuropathology (including NIIs) reminiscent of the R6\2 mice (Ordway et al 1997). Each human polyglutamine-associated disease shows a distinctive pattern of neurodegeneration yet the different mutant genes have very similar expression profiles in the body.…”
Section: Can Mice Model All Aspects Of Hd?mentioning
confidence: 99%